The barriers to linkage and retention in care for women living with HIV in an high income setting where they comprise a minority group. Issue 6 (3rd June 2019) - Giles, M. L.; MacPhail, A.; Bell, C.; Bradshaw, C. S.; Furner, V.; Gunathilake, M.; John, M.; Krishnaswamy, S.; Martin, S. J.; Ooi, C.; Owen, L.; Russell, D.; et al.
ABSTRACT: Women comprise a minority population of individuals living with HIV in Australia, and are often poorly represented in research and clinical trials so their needs remain largely unknown. Data suggests that they are diagnosed later than men and start antiretroviral therapy at a lower CD4 cell count. This raises the question whether there are sex specific barriers to linkage and retention in care. This study analyzed 484 surveys received from clinicians collecting demographic, virological, and reproductive health data along with perceived barriers to linkage and retention in care. Most women (67%) were estimated to have been linked into care within 28 days of diagnosis. For women who were not linked into care for more than 28 days, the most commonly reason cited was fear of disclosure to others, followed by fear of disclosure to their partner. The main reasons given for non-retention in care were related to transport, carer responsibilities, financial pressure, health beliefs and concern about stigma or disclosure.